Quaternary Lidocaine Derivatives: Past, Present, and Future - Wang Q; Zhang Y; Liu J; Zhang W (Dove Medical Press, 2021)
Qi Wang,1 Yujun Zhang,1 Jin Liu,1,2 Wensheng Zhang1,2 1Department of Anesthesiology, Laboratory of Anesthesia and Critical Care Medicine, Translational Neuroscience Centre, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2National-Local Joint Engineering Research Center of Translational Medicine of Anesthesiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Wensheng ZhangLaboratory of Anaesthesia & Critical Care Medicine, Translational Neuroscience Center, National-Local Joint Engineering Research Center of Translational Medicine of Anesthesiology, Sichuan University West China Hospital, Chengdu 610041, People’s Republic of ChinaEmail zhang_ws@scu.edu.cnAbstract: Local anesthetics have the advantage of complete analgesia with fewer side effects compared to systemic analgesics. However, their clinical use is limited due to their short duration of action. Thus, local anesthetics with fast onset, long duration of action, selective nociceptive block, and low local and systemic toxicity are highly desirable. In the past electrophysiological studies, quaternary lidocaine derivatives (QLDs) showed these characteristics. Here, we review electrophysiological properties of QLDs and their pharmacodynamic characteristics to shed light on potential problems.Keywords: lidocaine, local anesthetics, derivatives, QX-314